Controllable aggregation-induced emission based on a tetraphenylethylene-functionalized pillar[5]arene via host–guest recognition - Wu, Jie; Sun, Shu; Feng, Xiaoqing; Shi, Jianbing; Hu, Xiao-Yu; Wang, Leyong (Chemical communications (Cambridge, England), 2014)
A novel TPE-functionalized pillar[5]arene ( TPEP5 ) was successfully synthesized, and the motion of the TPE motif was restricted via pillararene-based host–guest recognition-mediated cross-linking, resulting in the efficient “turn-on” of fluorescence emission based on the AIE mechanism.